Tracing the geopolitical influences on the morphological and functional transformation in Guangdong merchant ships: Knowledge mining from the Ming and Qing maritime archives - Jinghui Ao; Miao Zhao; Weicong Li; Shengying Feng; Ziying Ye; Zilin Xu; Shanshan Ji (PLoS ONE, 2026)
Although the institutional history of ancient Chinese maritime trade has been extensively documented, the functional evolution of maritime vessels and their underlying drivers remains underexplored. Recent studies have moved beyond political explanations to explore the interplay of economic and technological dynamics. Using KH Coder for text mining, this study applies word frequency analysis and co-occurrence network modeling to investigate the geopolitical factors shaping the morphological evolution of Guangdong merchant ships in the Ming and Qing dynasties. A visual-comparative analysis further assesses the functional attributes of three representative ship types. Findings reveal that economic and military imperatives were the primary determinants of ship design, with political and geographic factors exerting secondary but supportive influence. For instance, increased piracy threats in the South China Sea prompted structural reinforcements for defensive purposes, while policy shifts under the Canton System encouraged hull designs optimized for high-capacity, long-distance trade. Guangdong’s maritime development was shaped largely by its strategic location and shipbuilding technologies. Ming-era vessels, constructed from teak and cedar, featured brightly painted, flat-bottomed hulls with elevated, streamlined prows. Qing-era ships employed lightweight alloys, muted color schemes, and reinforced double-planked hulls to enhance seaworthiness, while bow structures evolved into sharper and more angular forms. As Guangdong’s maritime trade transitioned from coastal routes to long-distance transoceanic networks—particularly with Europe—its ship design shifted progressively from broad and bulky to agile and eventually more durable configurations. These morphological transformations reflected not only external pressures, such as maritime security concerns and trade expansion, but also internal drivers, including institutional reforms and policy realignments that significantly influenced vessel design. This study contributes to the technical dimension of maritime historiography by emphasizing the merchant ship as an analytical nexus of institutional logic, technological systems, and geopolitical conditions. It offers both theoretical insight and methodological innovation for understanding the mechanisms behind ship design evolution and the spatial organization of premodern Chinese maritime networks.